HIV viral suppression and geospatial patterns of HIV antiretroviral therapy treatment facility use in Rakai, Uganda. (27th March 2018) - Billioux, Veena G.; Grabowski, Mary K.; Ssekasanvu, Joseph; Reynolds, Steven J.; Berman, Amanda; Bazaale, Jeremiah; Patel, Eshan U.; Bugos, Eva; Ndyanabo, Anthony; Kisakye, Alice; Kagaayi, Joseph; Gray, Ronald H.; et al.
Abstract : Objective: To assess geospatial patterns of HIV antiretroviral therapy (ART) treatment facility use and whether they were impacted by viral load suppression. Methods: We extracted data on the location and type of care services utilized by HIV-positive persons accessing ART between February 2015 and September 2016 from the Rakai Community Cohort Study in Uganda. The distance from Rakai Community Cohort Study households to facilities offering ART was calculated using the open street map road network. Modified Poisson regression was used to identify predictors of distance traveled and, for those traveling beyond their nearest facility, the probability of accessing services from a tertiary care facility. Results: In total, 1554 HIV-positive participants were identified, of whom 68% had initiated ART. The median distance from households to the nearest ART facility was 3.10 km (interquartile range, 1.65–5.05), but the median distance traveled was 5.26 km (interquartile range, 3.00–10.03, P  < 0.001) and 57% of individuals travelled further than their nearest facility for ART. Those with higher education and wealth were more likely to travel further. In total, 93% of persons on ART were virally suppressed, and there was no difference in the distance traveled to an ART facility between those with suppressed and unsuppressed viral loads (5.26 vs. 5.27 km, P  = 0.650). Conclusion: Distance traveled to HIV clinics was increased with higher socioeconomic status, suggesting that wealthier individuals exercise greater choice. However, distance traveled did not vary by those who were or were not virally suppressed. Abstract : Supplemental Digital Content is available in the text